Goldberger's cinical electrocardiography a simplified approach - Goldberger, Ary Louis, 1949- (Elsevier/Saunders, 2013)
Quickly grasp the fundamentals of ECG interpretation and analysis with Goldberger's Clinical Electrocardiography. Ideal for students and practicing clinicians alike, this accessible, concise cardiology reference offers relevant guidance on understanding rhythm disorders and their clinical outcomes. Trust Goldberger's Clinical Electrocardiography for all the in-depth coverage you need! Diagnose the key rhythm disorders that are relevant to today's clinical practice through expert pearls and advice.Easily navigate the full text online at www.expertconsult.com, and broaden your mastery of the material with online-only self-assessment ECGs and review questions.